Field Theory and Self-Organization - Martin , John Levi (Zeitschrift für Theoretische Soziologie, 2016)
Theories of self-organization in the social and behavioral sciences are now most commonly associated with systems theory. However, field theory puts forward a somewhat different species of selforganization. This conception, one which turns on the symmetric relations of free and largely interchangeable units, was inherent in the earliest work on magnetism, and was brought into the social and behavioral sciences by the Gestalt school. A reconsideration suggests that there may be times when the capacity of sets of units to self-organize may be seen as resulting from a field effect, as opposed to indicating the presence of a system in contradistinction to an environment.